The Emergence of Age-Friendly Communities: The City of Bangor - Sprague, Benjamin (Maine Policy Review, 2015)
Although Bangor now has the youngest median age of any city in Maine, Benjamin Sprague describes the city’s efforts to engage its older residents, which has led to Bangor being ranked one of the top places to retire by Forbes Magazine and AARP.